The Nordic Noir in Translation Database 2000–2020 - Berglund, Karl; Gulddal, Jesper; King, Stewart (Uppsala University, 2024)
This dataset contains bibliographic records of (in theory) all translations of Nordic crime fiction for adults, written in any of the five main Nordic languages (Danish, Finnish, Icelandic, Norwegian and Swedish) and published in translation during the period 2000–2020. The dataset is delimited to include only first edition translations published in print book form.

The dataset was originally published in DiVA and moved to SND in 2024.

This dataset contains bibliographic records of (in theory) all translations of Nordic crime fiction for adults, written in any of the five main Nordic languages (Danish, Finnish, Icelandic, Norwegian and Swedish) and published in translation during the period 2000–2020. The dataset is delimited to include only first edition translations published in print book form.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
The Nordic Noir in Translation Database 2000–2020
Keywords: nordic noir; nordic noir; Literature; Literature; translations; translations; sociology of translation; sociology of translation; crime fiction; crime fiction; General Literary studies; Litteraturvetenskap